Analysis of Risk Mitigation Measures in Housing Constraction Projects in Klaten District, Indonesia - Alhaqoni, Alfin Hakim; Priyanto, Budi (East Asian Journal of Multidisciplinary Research, 2023)
The population growth in Klaten Regency has increased by 3% over the last 5 years. This causes the need for housing to become a primary need for local communities. Because of this increase, there will be many housing development projects that will definitely need to take risk control or mitigation steps in housing construction with the aim of ensuring that housing development projects comply with planning. This research uses a quantitative research approach by conducting a data survey in the form of distributing questionnaires to 30 expert respondents. Then data processing and data analysis using descriptive methods to explain the results of data processing and analysis that have been carried out. From the results of research conducted and surveys of respondents, it was found that 25 risk control steps or mitigation steps were taken by developers in dealing with risk constraints in housing development projects. And of the 25 risk control steps or mitigation steps, there are 5 risk control steps or mitigation steps that are often carried out by developers when facing risk constraints in housing development projects.